Saint Kitts and Nevis. Significant achievements 2011 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Saint Kitts and Nevis during 2011 are identified, with respect to the needs and interests of the country, strengthening issues such as production, marketing, business development, greenhouses, operational plans, natural resource management, livestock , trade, water management, irrigation and youth inclusion.